Violation of the Teenagers-Computer Users' Binocular Vision and Pecularities of its Restoration - Nataliia Ulianytska; Stepan Vadziuk; Nataliya Byelikova; Svitlana Indyka; Oksana Usova (Lesya Ukrainka Volyn National University, 2017)
According to WHO experts, vision is vulnerable to computer loads. Computer users have complaints, combined by the terms «visual fatigue», «computer vision syndrome», which include a complex of violations in the system of refraction-accommodation. We did not find any research on the peculiarities of senior students' binocular vision with emmetropia when they are working with a personal computer, and therefore we decided to study this issue. 63 healthy school age senior students were examined, those with emmetropic refraction but without ophthalmic, somatic and psychological abnormalities. Chromatic angle of view and chromatic stereoscopy were studied with the help of special computer techniques. The survey was conducted in three stages. At the first stage, we studied the effect of a one-hour nonstop work in front of the computer monitor on the visual functions, at the second one - their state after a 15 minute passive rest. The third stage involved implementing our own program «Saving and Restoration of Vision» and determining the investigated parameters. The «Saving and Restoration of Vision» program contains special eye exercises, as well as those for the shoulder and neck with breath-holding elements. It is ascertained that high school students' one-hour work at the computer leads to deteriorating chromatic angle of view as well as chromatic stereoscopy. Herewith, the perfect match frequency of test objects decreased by 14,5 and 24,2 % respectively. Applying a set of rehabilitation exercises after a one-hour computer work allowed to restore the binocular vision to the original state, while a passive fifteen-minute rest after the computer visual load did not give such results. Thus, the study of senior students' binocular vision with emmetropic refraction, after one hour of work, showed its violation, which can be eliminated by a complex of rehabilitation exercises from the authors' program «Saving and Restoration of Vision».